Assessment of Earthworm Community Structure in Industrial and Non-industrial Soils - Verma, Falwinder; Singh, Sharanpreet; Singh, Jaswinder; Dhaliwal, Salwinder Singh; Parkash, Chander (Asian Journal of Biological and Life Sciences)
The trend of industrialization in all over the world significantly altered the assemblages of species and their surrounding environments in the soil. In the present study, the earthworm community structures were assessed in the industrial and non-industrial soils. Total seven earthworm species i.e. Amynthas morrisi (Beddard), Lampito mauritii (Kinberg), Metaphire posthuma (Vaillant) and Polypheretima elongata (Perrier) belonging to family Megascolecidae while Eutyphoeus incommodus (Beddard), Eutyphoeus waltoni (Michaelsen) and Octochaetona beatrix (Beddard) belonging to family Octochaetidae were reported. It was also reported that the earthworm species, their abundance and biomass was significantly (p < 0.05) higher in non-industrial soils as compared to industrial soils. The Metaphire posthuma was reported as the most abundant earthworm species in both industrial and non-industrial soils. The diversity indices such as the Shannon-Wiener diversity index, Simpson index of diversity and species richness index were higher in non-industrial soils while the Simpson index and species evenness index were high in industrial soils. The soil properties such as pH, EC, TDS and heavy metals content were much higher in the industrial soils and significant negative correlation of above said soil properties with earthworm ecological characteristics. This study can be considered as indication that industrialization has much more negative effects on the earthworms and their community structures.
Keywords: Correlation analysis; Diversity indices; Earthworm Ecological group; Relative abundance; Soil properties